Peranan Advokat Dalam Sistem Peradilan Pidana di Indonesia - Ismail Adha; Rio Bayu Riansyah Harahap; Fauziah Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
riminal justice is a system created to deal with crime problems that can disturb order and threaten people's sense of security, is one of the community's efforts to control crime so that it is within acceptable limits of tolerance. In the criminal justice system in Indonesia, it is known that there are four institutions that play a role, namely the police which act as an investigative and investigative agency, the prosecutor's office which acts as an institution that carries out prosecutions, the Supreme Court as an institution that oversees judges in the court environment, and Correctional Institutions. The existence of Advocates as law enforcers has been regulated in Article 5 of the Law of the Republic of Indonesia Number 18 of 2003 concerning Advocates. However, regarding the actual form and place of the Advocate's role as law enforcer, it is still unclear, especially in its role as a supporting component for the realization of an integrated criminal justice system, as a result, criminal law enforcement in Indonesia has not been optimal. This research uses normative legal research methods or literature studies, namely by analyzing UU.RI. No. 18 of 2003 concerning Advocates and UU.RI No. 8 of 1981 concerning Criminal Procedure Code (KUHAP), as well as other laws and regulations and library materials related to the role of Advocates to answer problems. The results of the study show that in terms of form and place, there are 2 (two) roles of advocates as law enforcers, namely (1) the role of advocates in the form of legal assistance to perpetrators based on Article 54 of the Criminal Procedure Code, (2) the role of advocates in the form of legal assistance to victims who regulated outside the Criminal Procedure Code. It is hoped that this will serve as input for law enforcers in upholding law and justice in Indonesia. Keywords: advocate, criminal justice